Epidemiological profile of morbidity and mortality due to heart failure in Brazil between 2013 and 2017 - Souza Júnior, Edison Vitório de (2020)
The purpose of this study was to describe the epidemiological profile of morbidity and mortality by heart failure in Brazil in the period from 2013 to 2017. Ecological and descriptive study conducted with data about heart failure from the Information Technology Department of the Unified Health System. The data were sex, age groups, race, hospitalization and deaths. For analysis of the data, it was adopted the simple descriptive statistical analysis (absolute and relative frequencies). During the quinquennium, it were registered 865.327 hospitalizations and 90.990 deaths, corresponding to a mortality rate of 10,52%. The southeast region has highlighted higher percentage of hospitalizations (41,66%), deaths (46,83%), and mortality rate (11,82%). The population aged ≥ 80 years old has been higher number of hospitalizations (21,95%), death (33,54%) and mortality rate (16,07%). The masculine sex obtained the higher number of hospitalizations (51,29%). However, the female sex exceeded the number of deaths in the male population (50,53%) and mortality rate (10,91%). The white color/race highlighted 37,08% of the hospitalizations and 36,62% of the deaths. In relation to the mortality rate, the indigenous population has been higher rate (11,04%). This study provides evidence about disparities in hospitalizations, deaths and mortality rates due to heart failure according to age, sex and color / race distributed in Brazilian regions, which reflects the difficulty that certain populations of ethnic groups have with regard to access health services and diagnosis through highly complex technologies. Thus, there is a need to implement preventive measures against pathology, promoting and protecting health especially for the indigenous population.